Spatial Correlation Between Land Development Level and Vulnerability Level of Mass Movement in the Watershed of Kayangan, Kulon Progo Regency, Yogayakarta Special Region - Junun Sartohadi; Rina Purwaningsih (Forum Geografi, 2004)
The objective of this research were: 1) to study the degree of soil development, and 2) to study the spatial correlation between the degree of soil development and the degree of mass movement susceptibility in the research area. The sampling method applied in this research was stratified sampling. Soil mapping units were applied as strata. The sample within strata was determined according the degree of mass movement susceptibility. The degree of soil development was determined using quantitative method of color indices and proflie index. The color indices were Buntley – Westin (B – W), Harden (H), and Hurst. The profile index was determined using solum, texture, structure, and soil consistency. The degree of mass movement susceptibility map was taken from PSBA UGM (2001). Spatial correlation between the soil development map and the mass movement susceptibility map was analyzed using “error matrix”. The result of this research indicated that the degree of soil development in the research area could be classified into three classes, i.e. class 1 (weakly develop soil); class 2 (moderately developed soil), class 3 (strongly developed soil). The degree of mass movement susceptibility was classified into three classes, i.e. class 1 (low susceptibility), class 2 (moderate susceptibility), and class 3 (high susceptibility). The result of error matrix calculation between mass movement susceptibility and soil development were 9.56%; 21.96%; 30.21% for BW + Ha, Hurst, and profile indices respectively. There values showed that there were low spatial correlations between the degree of soil development and mass movement susceptibility in the study area.